Fabrication, Characterization and Thermophysical Property Evaluation of SiC Nanofluids for Heat Transfer Applications - Nikkam, Nader; Saleemi, Mohsin; Haghighi, Ehsan B.; Ghanbarpour, Morteza; Khodabandeh, Rahmatollah; Muhammed, Mamoun; Palm, Björn; Toprak, Muhammet S. (Nano-Micro Letters, 2014)
Nanofluids (NFs) are nanotechnology-based colloidal suspensions fabricated by suspending nanoparticles (NPs) in a base liquid. These fluids have shown potential to improve the heat transfer properties of conventional heat transfer fluids. In this study we report in detail on fabrication, characterization and thermo-physical property evaluation of SiC NFs, prepared using SiC NPs with different crystal structures, for heat transfer applications. For this purpose, a series of SiC NFs containing SiC NPs with different crystal structure (α-SiC and β-SiC) were fabricated in a water (W)/ethylene glycol (EG) mixture (50/50 wt% ratio). Physicochemical properties of NPs/NFs were characterized by using various techniques, such as powder X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fouriertransform infrared spectroscopy (FTIR), dynamic light scattering (DLS) and Zeta potential analysis. Thermo-physical properties including thermal conductivity (TC) and viscosity for NFs containing SiC particles (α- and β- phase) weremeasured. The results show among all suspensions NFs fabricated with α-SiC particles have more favorable thermo-physical properties compared to the NFs fabricated with β-SiC.The observed difference is attributed to combination of several factors, including crystal structure (β- vs. α-), sample purity, and residual chemicals exhibited on SiCNFs. A TC enhancement of ∼20% while 14% increased viscosity were obtained for NFs containing 9 wt% of particular type of α-SiC NPs indicating promising capability of this kind of NFs for further heat transfer characteristics investigation.